INTERNET-TECHNOLOGY USAGE IN THE SYSTEM OF AUTONOMOUS BUSINESS ENGLISH LEARNING BY NON-LINGUISTIC STUDENTS - Svitlana V. Bodnar (Information technologies and learning tools, 2013)
The article highlights the problems of Internet-technology usage in the system of autonomous Business English learning by non-linguistic students. Different approaches which exist in contemporary pedagogical science as to defining the notion “autonomous learning” as a specific kind of educational-cognitive activity are considered. Attention is focused on the possibilities of IT technology usage in the process of autonomous foreign language learning at non-linguistic Universities. The advantages of World Wide Web usage in the process of foreign language learning are specified. The means of teaching and the kinds of independent work on foreign language learning by means of IT technology are presented in the article. The samples of tasks based on IT technology application are suggested